Urgensi Inklusifitas Pelaksanaan Dakwah di Tengah Problematika Sosial - Anja Kusuma Atmaja; Alfiana Yuniar Rahmawati (JURNAL ILMIAH SYI'AR, 2020)
The social problems that occur in society are certainly so complex if they have to be addressed one by one. A fact and reality that exist in everyday life are things that are an integral part of that situation. In digesting and seeking solutions to these social problems, as a Muslim everyone is required to be a solution in solving problems that exist and occur in social life itself. This study aims to describe in general the social problems that occur in people's lives by using the dakwah approach to solve them and to examine the problems using the library research method. The expected result of this research is to provide a general understanding to the public and readers in particular in order to interpret the importance of appreciating and accepting other people's opinions so that later the inclusiveness of society through da'wah can be a concept for solving these social problems.